2005
DOI: 10.1088/0268-1242/21/1/014
|View full text |Cite
|
Sign up to set email alerts
|

Passivation properties of CdS thin films grown by chemical bath deposition on GaSb: the influence of the S/Cd ratio in the solution and of the CdS layer thickness on the surface recombination velocity

Abstract: Evidences of the passivation effect are given when thin films of CdS are deposited on GaSb crystalline substrates, using a bath chemical deposition method. The passivation process is studied through photoacoustic and photoluminescence experiments. The surface recombination velocity calculated from photoacoustic measurements decreases and the radiative recombination rate as measured from photoluminescence spectra increases when the nominal S/Cd ratio in the layer deposition solution increases. The influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…This is because CdS has high transparency, wide and direct band gap transition (2.42 eV), photoconductivity, high electron affinity and n-type conductivity. CdS can also be used in a lot of applications including electronic [2] and optoelectronic devices [3]. Undoped and doped CdS thin films have been reported using different methods: electrodeposition (ED) [4], spray pyrolysis (SP) [5], chemical bath deposition (CBD) [6], molecular beam epitaxy (MBE) [7], metal organic vapour phase epitaxy (MOVPE) [8], successive ionic layer adsorption and reaction (SILAR) [9], and physical vapour deposition (PVD) [10].…”
Section: Introductionmentioning
confidence: 99%
“…This is because CdS has high transparency, wide and direct band gap transition (2.42 eV), photoconductivity, high electron affinity and n-type conductivity. CdS can also be used in a lot of applications including electronic [2] and optoelectronic devices [3]. Undoped and doped CdS thin films have been reported using different methods: electrodeposition (ED) [4], spray pyrolysis (SP) [5], chemical bath deposition (CBD) [6], molecular beam epitaxy (MBE) [7], metal organic vapour phase epitaxy (MOVPE) [8], successive ionic layer adsorption and reaction (SILAR) [9], and physical vapour deposition (PVD) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The III-V compound semiconductor gallium antimonide (GaSb) has in recent years attracted much attention as an important material for infrared (IR) optoelectronic and electronic device in the wavelength range 1-5 μm [1][2][3][4][5][6][7][8][9][10][11][12][13]. GaSb has an energy bandgap of 0.70 eV (1.77 μm) at room temperature (RT) and 0.81 eV (1.53 μm) at 4 K [14].…”
Section: Introductionmentioning
confidence: 99%
“…The endothermic peak at about 373 K in DSC spectrum, which is attributed to the elimination of water molecules, supports the presence of oxides on the as-milled sample surface. In a recent paper, Vigil-Galán et al [38] reported the formation of native oxides in as-grown GaSb samples in oxygen atmosphere and, in accordance with them the following chemical reaction occurs:…”
Section: Opc Photoacoustic Measurementsmentioning
confidence: 69%
“…According to Ref. [38], a fractional Sb monolayer is quite sufficient to increase the surface recombination velocity. In this study, the Sb segregation has occurred with annealing as it is shown in the XRD pattern.…”
Section: Opc Photoacoustic Measurementsmentioning
confidence: 96%